Testing of procedure for dangerous sections and maximum allowed power flows within them identification using testing scheme; Интеллектуальные энергосистемы; Т. 1 - Kradetskaya A. A. (Моделирование электроэнергетических сетей, 2013)
Заглавие с титульного экрана